2011
DOI: 10.1001/archsurg.2011.243
|View full text |Cite
|
Sign up to set email alerts
|

Choledochal Cyst and Associated Malignant Tumors in Adults

Abstract: To determine the clinical features and clinical outcomes of Korean adults treated surgically for choledochal cyst.Design: Retrospective nationwide multicenter study.Setting: Fifteen university hospitals (tertiary care referral centers) located in all 7 Korean provinces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
124
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(141 citation statements)
references
References 21 publications
9
124
0
8
Order By: Relevance
“…29,34,35 Additionally, APBDU is less commonly seen in choledochoceles in comparison with other types of CC, and patients are more likely to have undergone a previous cholecystectomy at the time of diagnosis. 10,17,36 In fact, given the distinct differences in presentation, clinical course, diagnosis, and pathophysiology, some authors argue that choledochoceles represent a different disease entity. 17,30,33 …”
Section: Incidence and Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations
“…29,34,35 Additionally, APBDU is less commonly seen in choledochoceles in comparison with other types of CC, and patients are more likely to have undergone a previous cholecystectomy at the time of diagnosis. 10,17,36 In fact, given the distinct differences in presentation, clinical course, diagnosis, and pathophysiology, some authors argue that choledochoceles represent a different disease entity. 17,30,33 …”
Section: Incidence and Epidemiologymentioning
confidence: 99%
“…5,104 Carcinogenesis is thought to occur via multistep genetic events where early K-ras and p53 mutations are seen in more than 60% of CC-related carcinomas 79,106-108 followed by a late occurring DPC-4 gene inactivation. 107 Most reported cases of malignant transformation are cholangiocarcinoma; however, gallbladder carcinoma is identified in 10% to 25% of CC-related malignancies 5,10,24,27,54 (Table 1). The presence of an APBDU is thought to play a role in carcinogenesis and hepatocellular damage due to reflux of pancreatic contents into the bile duct.…”
Section: Pathologic Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of BDD affected by a cancer are types I and IV according to Todani's classifi cation [ 2 ]; a cancer can be observed in all other types of BDD, but analysis of incidence is hindered by their rarity. In an analysis of a series of 63 biliary cancers on BDD, Todani et al [ 31 ] reported a tumor incidence of 68 % in type I, 5 % in type II, 1.6 % in type III, 21 % in type IV, and 6 % in type V. Recently a retrospective Korean multicenter study [ 32 ] reports a signifi cantly higher-incidence bile duct cancer in BDD type IVA (13/40, 32.5 %) and of gallbladder cancer in type I (28/35: 80 %). Presence of an ABPJ has a 16-55 % risk of malignancy, with or without congenital bile duct dilation [ 5 ].…”
Section: Evolutionmentioning
confidence: 99%